A comprehensive monitoring and evaluation framework for evidence to policy networks. (April 2022) - Kuchenmüller, Tanja; Chapman, Evelina; Takahashi, Ryoko; Lester, Louise; Reinap, Marge; Ellen, Moriah; Haby, Michelle M.
Abstract: Objective: To describe the development of a framework for monitoring and evaluating knowledge translation (KT) networks. Method: The framework was developed using mixed methods over four phases, including i) a targeted literature review of KT networks, activities and indicators, ii) two scoping reviews to further enhance the set of indicators, iii) peer-reviews by international KT experts and an online expert consultation, and iv) piloting. Results: A comprehensive theory of change (ToC) and indicators, both for the Network Secretariat and its participating member countries, were identified to develop the monitoring and evaluation framework. The framework includes (i) a ToC, including three key indicator domains across the results chain (outputs, short term outcomes, intermediate outcomes), and (ii) indicators for the three key domains, that can be selected depending on the stage of network maturity, along with suggested data collection methods. The three key indicator domains are 1) KT capacity and skill building; 2) network (structure, governance and leadership); and 3) KT/evidence-informed policy value and culture. Conclusion: The monitoring and evaluation framework that links KT activities with policy and health outcomes fills an important gap in optimizing KT procedures, generating lessons learned and increasing accountability of major multipartner KT networks. Highlights: To date, few evaluations of organizational or system-level activities exist promoting evidence-informed policy-making (EIP). The proposed monitoring and evaluation framework guides stakeholders in evaluating complex EIP initiatives. The framework presents a theory of change, logic models and indicators to assess research-to-policy activities. The suggested approach can be flexibly adapted and applied, depending on the unit of analysis and stage of network maturity.